2015
DOI: 10.1097/ncq.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Magnet Culture in Maintaining Quality Outcomes During Periods of Organizational Transition

Abstract: Organizational transition presents substantial risk to maintaining quality outcomes. The leadership style and culture present during periods of change and transition empower the frontline staff to react quickly and identify opportunities. The culture of Magnet develops the skill set that enables staff to be leaders in problem solving and identifying creative care delivery approaches. Objectives of this study were to analyze the impact of organizational transition on patient and staff satisfaction, quality, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…With change comes uncertainty and loss (Kotter , Shanley , Maxwell , Foltin & Keller , Gonzalez et al . ). Leaders must create an atmosphere of psychological safety where individuals feel safe to let go of previously held understandings and engage in new behaviors to test the waters of an emerging culture (Kavanagh & Ashkanasy , Foltin & Keller ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…With change comes uncertainty and loss (Kotter , Shanley , Maxwell , Foltin & Keller , Gonzalez et al . ). Leaders must create an atmosphere of psychological safety where individuals feel safe to let go of previously held understandings and engage in new behaviors to test the waters of an emerging culture (Kavanagh & Ashkanasy , Foltin & Keller ).…”
Section: Resultsmentioning
confidence: 97%
“…() and Gonzalez et al . () further support leading change as a process that requires distributed leadership, identifying the importance of empowering staff nurses to construct solutions that lead to a healthy and satisfied workforce. Bingham and Main () describe the role of staff nurses in leading change as driving quality improvement by gathering data and educating others through one‐on‐one and group communication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospitals (such as our academic health sciences center) undergoing restructuring and merger can negatively impact nursing working environments (Aiken, Clarke, & Sloane, ; Castner, Wu, & Dean‐Baar, ). Indeed, several studies have demonstrated that restructuring of hospitals and mergers of hospital systems can negatively impact nurses’ job satisfaction and increase burnout (Cummings, Hayduk, & Estabrooks, ; Gonzalez, Wolf, Dudjak, & Jordan, ; Teo, Pick, Newton, Yeung, & Chang, ).…”
Section: Discussionmentioning
confidence: 99%
“…There are at least three critical factors affecting the need to determine the quality of nursing: rapidly increasing health‐care costs and great competition, which made the equalize of quality and cost one of the most important issues in health‐care organizations (Gonzalez et al. ).…”
Section: Introductionmentioning
confidence: 99%